KAJIAN SEMIOTIKA KONOTASI ORNAMEN BETAWI GIGI BALANG - Muhammad Syukri Faiz; Acep Iwan Saidi; Ganal Rudiyanto (Universitas Trisakti, 2020)
The connotation semiotical study of the Betawi’s gigi balang ornament discusses the meaning of the gigi balang ornament which has begun to be revived by the DKI Jakarta provincial government. The study of meaning is expected to be a guideline that an ornament is not only an art but can affect people’s lives. With the connotative semiotic method, the meaning of gigi balang does not only stop until the connotative meaning but until the mythic meaning which is held firmly by the Betawi people.